Pengaruh variasi ketebalan saluran dan temperatur tuang terhadap fluiditas dan porositas hasil pengecoran kuningan pada pengecoran evaporatif - Sugita, I.K.; Mara, M.; Priambadi, I.G.N.; Nuarsa, I.M. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2023)
The development of foundry technology continues to grow along with the increasingly complex needs for making products based on art and culture, one of which is sclupture. Evaporative casting based on non-permanent patterns made of polystyrene foam, with the advantage of precision casting results in complex shapes. The purpose of this study was to determine how variations in the pouring channel and pouring temperature affect the fluidity and porosity of brass castings in evaporative casting. Casting was carried out in castings with thicknesses of 1.5, 2, 3, 4, and 5 mm at pouring temperatures of 900°C, 950°C, and 1000°C using brass with a composition of Cu60% and Zn40%. The highest fluidity was found at a pattern density of 0.012 gr/cm3 at a pouring temperature of 1000°C with a flow length of 150 mm, while the lowest fluidity was obtained at a pattern density of 0.016 gr/cm3 at a pouring temperature of 900°C with a flow length of 13 mm. The results of scanning electron microscope (SEM) observations can be observed in spesimens with a density of polystyrene foam and a high casting temperature, an increase in the porosity formed.